Proposition 48 and a Division II Institution - Lyons, Donna M. (My University, 1989)
This was a study of 96 football and 12 men's basketball athletes at one Division II institution in New England that does not award scholarships. The study sought to determine how the athletes in the study would have been classified in terms of the new Proposition 48 eligibility rules had they been in place when the students were freshmen. In this group, they found there would be 90 qualifiers, 15 partial qualifiers and 3 non-qualifiers, which they considered low compared to NCAA Research Committee survey results.
Keywords: eligibility; Division II